Looking Backward, Looking Forward: Institutional Responses and Instructional Changes to Address COVID-19 Among A Rural Midwestern University (International Journal of Multidisciplinary Perspectives in Higher Education, 2024)
In response to COVID-19, post-secondary institutions made swift changes, one of which was the widespread transition to online and remote learning to address the immediate effects of the disruption in the teaching and learning environment at the higher education level. This was a period of quick pivoting at both course as well as the leadership levels across universities, ranging from institutional leaders to class instructors. The current study takes a qualitative approach in mapping the changes and challenges in the areas of responses to students’ psychological needs, responses to students’ academic needs, and responses to minoritized students’ needs from institutional leaders’, teaching faculties’, and teaching assistants’ perspectives. The results suggest that institutional leaders and instructors perceived a decrease in academic motivation and increase in social isolation among students during COVID-19. The results also highlight the unique difficulties faced by students from minoritized backgrounds from institutional leaders’ and instructors’ perspective. The study confirms the need for institutional leaders and faculties to take actions and provide support to minoritized students even in post-pandemic higher education. Implications and guidance on future university policies and programs to help preserve educational quality of instruction and mitigate educational inequities as a result of the pandemic are also discussed.